2020
DOI: 10.1002/wer.1413
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production by co‐digestion of municipal wastewater and food waste: Performance in semi‐continuous and continuous operation

Abstract: Municipal wastewater has recently attracted interest in relation to anaerobic wastewater treatments. Biogas production with co‐digestion of mixed substrates has been proposed and has many potential benefits for municipal wastewater. The aim of this research was to assess the performance of biogas production during co‐digestion of municipal wastewater and food waste under semi‐continuous and continuous operation with various hydraulic retention times (HRTs). A laboratory‐scale continuous stirred tank reactor (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…This showed that codigestion with EFB wastewater could increase the methane production efficiency compared with the control set (experiment set 3), revealing codigestion of 50% POME + 50% seed without EFB wastewater, with a value of 0.093 ± 0.013 L CH4/g VS removed or 0.0078 ± 0.001 L CH4/g VS added. The results demonstrate that codigestion could increase the methane production efficiency up to twofold (Figures 3 and 4), which was consistent with other studies on codigestion to increase the methane production efficiency [9,19,21,22] Upon analyzing the default parameters listed in Table 6, decreasing the volume of POME resulted in a reduced amount of initial volatile fatty acid (VFA) while increasing the quantity of inoculum. Typically, the recommended range for VFA is between 50 and 500 milligrams per liter of CH3COOH, with the maximum permissible value of 2000 milligrams per liter of CH3COOH in the system [23].…”
Section: The Study Of Codigestion Of Pome and Efb Wastewater At Vario...supporting
confidence: 90%
See 1 more Smart Citation
“…This showed that codigestion with EFB wastewater could increase the methane production efficiency compared with the control set (experiment set 3), revealing codigestion of 50% POME + 50% seed without EFB wastewater, with a value of 0.093 ± 0.013 L CH4/g VS removed or 0.0078 ± 0.001 L CH4/g VS added. The results demonstrate that codigestion could increase the methane production efficiency up to twofold (Figures 3 and 4), which was consistent with other studies on codigestion to increase the methane production efficiency [9,19,21,22] Upon analyzing the default parameters listed in Table 6, decreasing the volume of POME resulted in a reduced amount of initial volatile fatty acid (VFA) while increasing the quantity of inoculum. Typically, the recommended range for VFA is between 50 and 500 milligrams per liter of CH3COOH, with the maximum permissible value of 2000 milligrams per liter of CH3COOH in the system [23].…”
Section: The Study Of Codigestion Of Pome and Efb Wastewater At Vario...supporting
confidence: 90%
“…The batch experiments were conducted using the following steps: all three types of fermentable materials were brought to room temperature before conducting the experiment, the three types of fermentable materials were separated and placed in a container, the volume of each fermentable material was measured and combined according to the ratio calculation of the COD/N (chemical oxygen demand/nitrogen) ratio [9], using cofermentable materials in the ratios of 2.5, 5, and 10% v/v, and the fermentation material was added to the anaerobic digestion system as a one-time feeding. Then, the starting inoculum was used at 20, 35, 50, and 75% of the working volume of the fermentation material to determine the appropriate proportion of the microorganisms in gas production (Table 1) as recommended by [10].…”
Section: Batch Experimentsmentioning
confidence: 99%
“…Haryanto et al (2018) [30] have operated anaerobic digestion with different hydraulic retention times (HRTs), namely 7, 14, 21, 28 and 35 days, with substrate concentration of 16 g/L of total solids (TS), and at the mesophilic temperature of 37 • C. They have noticed that the biogas volume of HRT 14 was quite similar to biogas volume of HRT 21, 28 and 35 days. Additionally, APHA (2012) [28] and Ounsaneha et al (2021) [63] found that the optimum conditions for anaerobic digestion of FW were achieved in a reactor with an HRT of 12 days, which was similar to the optimum HRT found in this study. The methane content in biogas for biofilm hydrolyzed food waste was analyzed and it was 62-67% of methane.…”
Section: Optimum Hrt For Anaerobic Digestion By Ofatsupporting
confidence: 83%
“…The study's findings in terms of wastewater treatment efficiency, biogas output, and economic analysis results demonstrated that the HFAR can compete with existing industrial technologies for food wastewater treatment [31]. Ounsaneha et al [32], evaluated biogas generation during the digestion of municipal wastewater and food waste in semi-continuous and continuous operation with varying hydraulic retention times (HRTs). At 30 days of HRTs with a 10:90 ratio of municipal wastewater to food waste, methane outputs of 167.41 66.52 ml/g-Vs were observed in semi-continuous mode.…”
Section: Resultsmentioning
confidence: 99%